On the Impact of Regulating Commissions : Evidence from the Indian Mutual Funds Market - Santosh, Anagol; Marisetty, Vijaya; Sane, Renuka; Buvaneshwaran, Venugopal (Published by Oxford University Press on behalf of the World Bank, 2018)
Commissions-motivated agents have historically helped the development of many markets, but research suggests brokers motivated by commissions sometimes steer consumers towards inappropriate products. This issue is particularly important in household financial markets where consumers may be unable to evaluate products on their own. While reforms attempting to limit commission payments have been undertaken worldwide, little research has evaluated the impact of these reforms. We study a major Indian investor protection reform that attempted to reduce commissions tied to mutual fund sales by banning the distribution fees that mutual funds had previously earmarked for commissions. We analyze the policy impact by comparing funds charging high versus low distribution fees pre-reform and find no evidence that the reform itself reduced fund flows. We argue that the most plausible explanation is that the Indian asset management industry maintained substantial commissions to brokers through other revenue sources apart from the banned distribution fees.